Family Centered Care Intervention Effectively Reduces Parental Anxiety in Perinatology Ward - Utario, Yossy; Rustina, Yeni; Efendi, Defi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Separation due to hospitalization and the condition of infant diseases can cause stress and anxiety in parents.Parental anxiety can affect the parent-infant relationship and cause developmental problems in infant. FamilyCentered Care (FCC) is an effort to reduce parental anxiety when infants undergo treatment. This study aimedto identify the effect of FCC intervention on parents' anxiety in the perinatology ward. This study used aquasiexperimental design with one group pretest posttest design. A total of 29 parents were recruited byconsecutive sampling technique, with following inclusion criteria: parentsof infants who were undergoingtreatment in the perinatology ward, infants who were not immediately intubated when admitted to theperinatology ward, willing to become respondents, able to read and write; Meanwhile, the exclusion criteriawere parents who did not follow the intervention process until the end of the intervention, and infants who wereintubated during the intervention process. The intervention was carried out by providing FCC education andinvolving families for 3 days of baby care. Parental anxiety measurements were carried out before and after theintervention using the Parental Stressor Scale-NICU (PSS-NICU) questionnaire. The data analysis usedWilcoxon test. The results of this study showed that there was a significant difference in the mean anxiety ofparents before and after the FCC intervention (p = 0.001). FCC intervention is effective in reducing parentalanxiety. It is recommended that this intervention can be applied to the parents from the beginning of thetreatment in perinatology ward.